Genetic Variation and Phylogenetic Tree of Indonesian domestic Goat - Hartatik, Tety (2015)
Indonesia has native domestic goat breeds as genetics resources, however so far there were limited informations of genetic diversity, population demographic history, and origin of Indonesian goats. The aim of this study was to examine the genetic diversity and phylogenetic tree of Indonesian domestic goats which compared with available data in Genbank. Polymerase Chain reaction from 20 individuals representing 4 indigenous breeds was performed to determine a 464-bp fragment of mitochondrial DNA (mtDNA) cytochrome b. Restriction fragment length polymorphism of 464 bp using Hinf and HaeIII show the similar fragment result in 2% Agarose gel. Two representative products PCR were sequenced for further analysis. The sequence results then aligned with 37 data genbank by using BioEdit version 7.0. These results pattern of genetic variation in goat’s mtDNA sequences indicated 79 SNP contains substitution G → A (25 SNP), T → C (46 SNP), A → T (4 SNP) and 5 SNP of insertions/deletions. Phylogenetic tree analisis shows the distinct group of Indonesian goats compare with 37 individual data form genbank which clustered into two larger lineages. The genetic variation of domestic goats in Indonesia gives more contribution to the genetic diversity of animal in the world.